2009
DOI: 10.1016/j.ajog.2008.08.064
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced estrogen-induced proliferation in obese rat endometrium

Abstract: Objective-We tested the hypothesis that the proliferative estrogen effect on the endometrium is enhanced in obese versus lean animals. Study design-UsingZucker fa/fa obese rats and lean control, we examined endometrial cell proliferation and the expression patterns of certain estrogen-regulated pro-proliferative and antiproliferative genes after short-term treatment with estradiol.Results-No significant morphological/histological difference were seen between the obese rats and the lean rats. Estrogen-induced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 28 publications
0
23
0
4
Order By: Relevance
“…Specifically, we showed that the expression of the pro-proliferative genes was increased while the expression of anti-proliferative genes were inhibited in the endometrium of estrogen-treated obese, insulin-resistant rats as compared to lean controls 5 . These data suggested that insulin potentiates estrogen-regulated endometrial proliferation in the context of obesity.…”
Section: Introductionmentioning
confidence: 88%
“…Specifically, we showed that the expression of the pro-proliferative genes was increased while the expression of anti-proliferative genes were inhibited in the endometrium of estrogen-treated obese, insulin-resistant rats as compared to lean controls 5 . These data suggested that insulin potentiates estrogen-regulated endometrial proliferation in the context of obesity.…”
Section: Introductionmentioning
confidence: 88%
“…Our group has demonstrated that the proliferative effect of estrogen on the endometrium is enhanced in obese versus lean animals 35 . Using the Zucker rat model of hyperinsulinemia, estrogen induced significantly higher expression of the proproliferative genes, cyclin A and c-myc and in endometrium of obese rats, as compared that observed in lean control animals.…”
Section: Type 2 Diabetes and Hyperinsulinemiamentioning
confidence: 94%
“…Preclinical studies conducted by our group suggest that hyperinsulinemia and insulin resistance associated with obesity may contribute to endometrial proliferation. 13 In addition, we have found that correction of hyperinsulinemia with insulin-sensitizing agents reverses the proliferative drive (unpublished data). Given the high prevalence of insulin resistance in our population of patients and potential contribution of IR to the carcinogenesis of endometrial cancer, insulin-sensitizing agents may have a role in treatment and prevention of this disease.…”
Section: Commentmentioning
confidence: 87%
“…912 Additionally, preclinical studies have shown that insulin resistance accompanied by high circulating levels of insulin potentiates the effect of estrogen on endometrial proliferation. 13 Thus, insulin resistance may further clarify the link between obesity and endometrial cancer. We hypothesized that the risk of endometrial cancer associated with diabetes alone results in an underestimation of the true relationship between IR and endometrial cancer.…”
Section: Introductionmentioning
confidence: 99%